Pola Pendekatan Manajemen Berbasis Madrasah (Mbm) Di Madrasah Ibtidaiyyah - Elga Yanuardianto (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2021)
In the era of madrasa independence, especially in MI and the era of Madrasah-Based Management (MBM), the first and foremost task and responsibility of madrasah leaders is to make the madrasas they lead more effective, in the sense of becoming more useful for the madrasa itself and for the community. the wider community of users. In order for the duties and responsibilities of the madrasah leaders to become real, it would be necessary for them to understand, explore, and apply some of the concepts of management science that have been developed by thinkers in the business world. When seriously deepened, the concepts of management science may have value (in terms of values) that will not plunge our world of education into a business that can harm or disappoint the wider community of its users. MBM is one form of education reform, which offers schools to provide better and adequate education for students. Autonomy in management has the potential for schools to improve staff performance, offer direct participation to relevant groups and increase public understanding of education. In line with the spirit and spirit of decentralization and autonomy in the field of education, school authority also plays a role in accommodating the general consensus that believes that wherever possible decisions should be made by those who have the best access to local information, who are responsible for implementing policies and who are affected by policies. the policy. So that MI which uses madrasah-based management has the authority to regulate its own madrasa in order to achieve its goals. In other words, the MI has the right to empower its potential, both the potential of madrasa residents and the potential of the community. Thus, the leadership and governance that is owned must support the success of the goals that have been set.